REFORMASI BIROKRASI MELALUI PENERAPAN MANAJEMEN KONTRAK SEBAGAI UPAYA MEWUJUDKAN NETRALITAS PEGAWAI NEGERI SIPIL DALAM ERA OTONOMI DAERAH - Rosfiah Arsal (Jurnal Manajemen Kepegawaian, 2009)
Sentralistic power have made of bureaucracy officials are fail to respond of economic and politics crisis because street-level bureaucrats not have authority and creativity to take in hand of economic and social problems. Paternalistic bureucracy and power concentrate on higher officials and social services concentrate on lower officials. Not drive and incentive for efficiency and responsive. Culture and competitive traditions not develop. Contract management is one of element in bureaucracy that regulate of relationship pattern between higher officials and lower officials. Relationship pattern between officials have not openness and rightness so that have potential to make corruption, collution and nepotism. Purposes of contract management models for increase of performances and neutralities of public servan with partnerships equity between higher officials and lower officials. Besides as of personnel admistration models so alternative model to increase of budgeting performance. If this model implemented, the first possible resistant is Governor, Regent and the other higher officials because they have big power for budgeting and personnel policy, second the officias that have not capacities and capabilities have visi and mission, to make programs because they have not competention, skill and knowledgeKata-kata kunci: Bureaucracy reform, partneship of equity, contract management